In search of lost ergots: phylogenetic re-evaluation of Claviceps species in Japan and their biogeographic patterns revealed - Tanaka, E; Tanada, K; Hosoe, T; Shrestha, B; Kolařík, M; Liu, M (Studies in mycology, 2023)
Claviceps (Clavicipitaceae, Hypocreales) was erected in 1853, although ergotism had been well-known for a much longer time. By 2000, about 70 taxa had been described in Claviceps, of which eight species and six varieties were based on Japanese type or authentic specimens. Most of these Japanese Claviceps taxa are based on lost specimens or have invalid names, which means many species practically exist only in the scientific literature. The ambiguous identities of these species have hindered taxonomic resolution of the genus Claviceps. Consequently, we sought and collected more than 300 fresh specimens in search of the lost Japanese ergots. Multilocus phylogenetic analyses based on DNA sequences from LSU, TEF-1α, TUB2, Mcm7, and RPB2 revealed the phylogenetic relationships between the Japanese specimens and known Claviceps spp., as well as the presence of biogeographic patterns. Based on the phylogenetic analysis, host range and morphology, we re-evaluated Japanese Claviceps and recognised at least 21 species in Japan. Here we characterised 14 previously described taxa and designated neo-, lecto- and epi-types for C. bothriochloae, C. imperatae, C. litoralis, C. microspora, C. panicoidearum and C. yanagawaensis. Two varieties were elevated to species rank with designated neotypes, i.e. C. agropyri and C. kawatanii. Six new species, C. miscanthicola, C. oplismeni, C. palustris, C. phragmitis, C. sasae and C. tandae were proposed and described. Taxonomic novelties: New species: Claviceps miscanthicola E. Tanaka, Claviceps oplismeni E. Tanaka, Claviceps palustris E. Tanaka, Claviceps phragmitis E. Tanaka, Claviceps sasae E. Tanaka, Claviceps tandae E. Tanaka; New status and combination: Claviceps agropyri (Tanda) E. Tanaka, Claviceps kawatanii (Tanda) E. Tanaka; Typifications (basionyms): Lecto- and epitypification: Claviceps yanagawaensis Togashi; Neotypifications: Claviceps purpurea var. agropyri Tanda, Claviceps bothriochloae Tanda & Y. Muray, Claviceps imperatae Tanda & Kawat., Claviceps microspora var. kawatanii Tanda, Claviceps litoralis Kawat., Claviceps microspora Tanda, Claviceps panicoidearum Tanda & Y. Harada; Resurrection: Claviceps queenslandica Langdon. Citation: Tanaka E, Tanada K, Hosoe T, Shrestha B, Kolařík M, Liu M (2023). In search of lost ergots: phylogenetic re-evaluation of Claviceps species in Japan and their biogeographic patterns revealed. Studies in Mycology 106: 1-39. doi: 10.3114/sim.2022.106.01.
Keywords: Phylogeny; Hypocreales; Neotypification; Clavicipitaceae; New taxa; Systematics; Taxonomy